Predicting women's career decisiveness in the ICT sector: A serial multiple mediation model among MIS students. - Nuray Akar; Tayfun Yörük; Ömür Tosun (PLoS ONE)
This study explores the factors that influence women's career decisions in the Information and Communication Technologies (ICT) sector, as perceived by women Management Information Systems (MIS) students. It examines how career optimism (CO) and perceived employability (PE) affect the link between irrational beliefs about employment (IB) and career decisiveness (CD). The study involved 232 female students from ICT-related programs in Turkey. Data were collected using four different scales and analyzed for accuracy and connections between factors. To prevent the effects of common method bias, Harman's single-factor test was used, followed by an analysis of mediation effects. Results showed that women students' IB about employment negatively impacted their CD. CO helped mediate this effect. Moreover, both CO and PE together had a mediating role in how IB affected CD. These findings offer valuable insights into the individual and contextual factors shaping women's career decisions. They also support initiatives to boost women's career stability, which aligns with the United Nations (UN) Sustainable Development Goals (SDGs) 5 and 8. Encouraging career optimism and employability may reduce the negative effects of IB and contribute to a fairer job market where women can pursue ambitious careers.